An exploration of South African Muslim general practitioners perceptions of mental illness within Lenasia, a suburb of Johannesburg. - Mohamed, Zaakiyah (My University, 2013)
General practitioners (GP’s) are often the first point of entry when seeking medical treatment. They are responsible for treating members of the community and thus their understanding and conceptualisation of mental illness will influence patient care. Additionally, GP’s religious and cultural affiliations play an influential role in the aetiology and treatment of mental illness. Thus this study explored perceptions of mental illness in a sample of 10 Muslim GP’s (5 male, 5 female) of Indo-Pak ancestry in the Lenasia area (Johannesburg, South Africa). Semi structured interviews were conducted with each GP which entailed 37 questions related to the GP’s context, GP’s perceptions of mental illness, the understanding of religion and culture, the treatment of mental illness and the aspect of spiritual illness. Thematic content analysis was used to analyse the data. From the results obtained, eight themes were salient; namely definitions and aetiology of mental illness as understood by GP’s, the role of culture, the assimilated identity, Islamic beliefs regarding mental illness, GP’s beliefs regarding spiritual illness, collaboration and referral to other healthcare professionals and finally influential factors affecting GP’s. Based on the above themes it can be concluded that more awareness regarding the stigmatization of mental illness needs to be addressed. Furthermore, it is vital that healthcare professionals possess an understanding of the use of traditional healing as a mode of treatment amongst certain South African population groups. This study therefore paves the way for further research regarding the incorporation of cultural beliefs into mainstream theory.
Keywords: Islam; Mental illness; Culture; Religion; Stigma; Spiritual illness; Traditional healing